Komoditas Tembakau Besuki Na-Oogst dalam Perspektif Pembangunan Berkelanjutan di Kabupaten Jember - Rhamanda Try Muktianto; Herman Cahyo Diartho (Caraka Tani: Journal of Sustainable Agriculture, 2018)
Tobacco commodities Besuki Na-Oogst in Jember regency of production continue to decrease. The decline in tobacco production Besuki Na-Oogst caused by erratic weather, high rainfall, volcanic ash mounts roar. The purpose of this research to analyze the sustainability status of tobacco commodities Besuki Na-Oogst seen from the ecological, economic, and social dimension. The method of analysis used in this research is descriptive method and RAP-Tobacco analysis with Multidimensional scaling method. The result of the research shows that the agribusiness system of tobacco commodities Besuki Na-Oogst is still not related, the relationship between subsystems of supply of production facilities, cultivation subsystem or farming and supporting service subsystem still not close. The sustainability status of multi-dimensional Na-Oogst tobacco commodities including ecological, economic, and social dimensions shows that tobacco Besuki Na-Oogst commodities are on a sustainable status with an index value of 58.27 which means the index values are all dimensions including: ecological, economic dimension, and social effect on the sustainability status of tobacco commodities besuki Na-Oogst and most farmers in Wuluhan sub-district still want to grow besuki Na-Oogst tobacco.